Karyotypic diversity in four species of the genus Gymnotus Linnaeus, 1758 (Teleostei, Gymnotiformes, Gymnotidae): physical mapping of ribosomal genes and telomeric sequences - Scacchetti, Priscilla Cardim [UNESP]; Pansonato-Alves, Jose Carlos [UNESP]; Utsunomia, Ricardo [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Zoological Inst, 2011)
Conventional (Giemsa, C-Banding, Ag-NORs, CMA3) and molecular (5S rDNA, 18S rDNA, telomeric sequences) cytogenetic studies were carried out in specimens of ten distinct fish populations of the genus Gymnotus (G. sylvius Albert and Fernandes-Matioli, 1999, G. inaequilabiatus Valenciennes, 1839, G. pantherinus Steindachner, 1908, and G. cf. carapo Linnaeus, 1758) from different Brazilian hydrographic basins. G. sylvius presented a diploid number of 40 chromosomes (22m+12sm+6st), G. pantherinus presented 52 chromosomes (32m+18sm+2st), while G. inaequilabiatus (42m+10sm+2a) and G. cf. carapo (38m+12sm+4st) presented 54 chromosomes. The C-banding technique revealed centromeric marks in all chromosomes of all species. Besides that, conspicuous blocks of heterochromatin were found interstitially on the chromosomes of G. inaequilabiatus, G. cf. carapo, and G. pantherinus. All four species showed single nucleolus organizing regions confirmed by results obtained through Ag-NORs and FISH experiments using 18S rDNA probes, which showed the NORs localized on the first chromosome pair in G. inaequilabiatus, G. cf. carapo, and G. pantherinus, and on pair 2 in G.sylvius. CMA(3) staining revealed additional unrelated NORs marks in G. sylvius and G. pantherinus. The 5S rDNA probes revealed signals on one pair in G. sylvius and two pairs in G. pantherinus; G. inaequilabiatus had about seventeen pairs marked, and G. cf. carapo had about fifteen pairs marked. It is considered that the high amount of heterochromatin identified in the chromosomes of G. inaequilabiatus and G. cf. carapo could have facilitated the dispersion of SS rDNA in these species. Interstitial signals were detected on the first metacentric pair of G. sylvius by telomeric probes (TTAGGG)n indicating the possible occurrence of chromosomal fusions in this species. The present study reveals valuable cytotaxonomic markers for this group and allows a more precise evaluation of the processes involved in the karyotype differentiation and the interrelationships among different species of the genus Gymnotus.
Keywords: FISH; rDNA; cytogenetics; heterochromatin; chromosomal rearrangements